Pollution Absorbing Plant Design in Public Space Using Vertical Garden Method - Azi Ilham Anshori; Ghia Tri Jayanti (Universitas Pendidikan Indonesia (UPI), 2022)
Humans are living beings who have a social spirit and depend on their surroundings, including the natural environment, which has a reciprocal relationship to the ecosystem of life. Natural damage is a characteristic of disruption of an environment caused by various irresponsible activities that have an impact on all things that can harm various parties. The emergence of forest fires, waste smoke from industrialization activities, carbon fumes from vehicles have become quite serious problems for the environment and health so that they become an urgency that must be resolved, especially the increasingly emergency condition of the earth due to global warming. In this study aims to describe and develop the design of pollution absording plant designs with the vertical garden method considering that it is an anticipatory step to save the environment. The resulting product has a new value offered and a high use value so that it can be used as an innovation to the environment, the use of environmentally friendly and easy materials and systems so that it becomes an advantage of the product. This design process includes various stages, namely problem formulation, data analysis, solution formulation, design development in the from of initial sketches, design development, and final design. It is hoped that the application of this designed product in public places will create a green city concept “Green City” which will change the condition and situation of a healthy and clean city free from pollution.